System Information And Application For Official Marriage Trials For Polri & PNS Members At Polda Bengkulu - Wahyu Hidayat; Diana Diana; Muhammad Husni Rifqo; Dwita Deslianti (Penerbit Jurnal Indonesia, 2023)
One of the stages for forming a family within the Police environment, is that each prospective bride and groom will undergo a marriage coaching session. At the Bengkulu Regional Police level, this official marriage trial is under the auspices of the Human Resources Bureau (HR). Currently, the management of files and scheduling of service marriage sessions within the Bengkulu Police is still being done manually by physically collecting the required files and processing them by the admin. The purpose of this practical work is to design and build a system that can assist in the process of applying for official marriage hearings for members of the Police & Civil Servants at the Bengkulu Regional Police. The system development method in this study uses the waterfall model. Process design on the system using DFD (Data Flow Diagram), database design using ERD (Entity Relation Diagram) and database design using MySQL.The result of this research is an information system and application for official marriage hearings for members of the National Police & Civil Servants at the Bengkulu Regional Police which can assist in the process of filing for official marriage hearings. And conduct testing of the system using the blackbox method.